Peritumoral Brain Edema in Metastases May Be Related to Glymphatic Dysfunction - Toh, Cheng Hong; Siow, Tiing Yee; Castillo, Mauricio (Frontiers in Oncology, 2021)
Objectives: The proliferation of microvessels with increased permeability is thought to be the cause of peritumoral brain edema (PTBE) in metastases. The contribution of glymphatic system to the formation of PTBE in brain metastases remains unexplored. We aimed to investigate if PTBE volume of brain metastases is related to glymphatic dysfunction. Materials and Methods: 56 patients with brain metastases who had preoperative dynamic susceptibility contrast-enhanced perfusion-weighted imaging for calculation of tumor cerebral blood volume (CBV) and diffusion-tensor imaging for calculations of tumor apparent diffusion coefficient (ADC), tumor fractional anisotropy (FA) and analysis along perivascular space (ALPS) index were analyzed. Volumes of PTBE, whole tumor, enhancing tumor, and necrotic and hemorrhagic portions were manually measured. Additional information collected for each patient included age, sex, primary cancer, metastases location and number, and the presence of concurrent infratentorial tumors. Linear regression analyses were performed to identify factors associated with PTBE volume. Results: Among 56 patients, 45 had solitary metastasis, 24 had right cerebral metastasis, 21 had left cerebral metastasis, 11 had bilateral cerebral metastases, and 11 had concurrent infratentorial metastases. On univariable linear regression analysis, PTBE volume correlated with whole tumor volume (β = -0.348, P = 0.009), hemorrhagic portions volume (β = -0.327, P = 0.014), tumor ADC (β = 0.530, P < .001), and ALPS index (β = -0.750, P <.001). The associations of PTBE volume with age, sex, tumor location, number of tumors, concurrent infratentorial tumor, enhancing tumor volume, necrotic portion volume, tumor FA and tumor CBV were not significant. On multivariable linear regression analysis, tumor ADC (β = 0.303; P = 0.004) and ALPS index (β = -0.624; P < 0.001) were the 2 independent factors associated with PTBE volume. Conclusion: Metastases with higher tumor ADC and lower ALPS index were associated with larger peritumoral brain edema volumes. The higher tumor ADC may be related to increased periarterial water influx into tumor interstitium while lower ALPS index may indicate insufficient fluid clearance. The changes in both tumor ADC and ALPS index may imply glymphatic dysfunction, which is at least partially responsible for peritumoral brain edema formation.